ANALISIS PERAN METODE ROLE PLAY DALAM PENGEMBANGAN KETERAMPILAN SPPEAKING BAHASA INGGRIS - Hafizha Sitta Imana; Desty Surya Khairunnisak; Wiwin Luqna Hunaida (STKIP Subang, 2026)
Speaking is one of the key aspects of English language proficiency. In an educational context, speaking skills are a primary focus at various levels of education. This study aims to analyze the role of one teaching method role-play in the development of English speaking skills. This study is based on the finding that many students still struggle with speaking English, such as expressing ideas, answering questions, and engaging in simple conversations. This study uses a qualitative approach based on a literature review. Data were collected from books, scientific journals, and previous studies on the application of the role-play technique. Research findings indicate that the role-play method has several advantages, including improving students’ speaking skills, boosting self-confidence, creating a pleasant learning atmosphere, increasing participation, aiding vocabulary acquisition and pronunciation, fostering cooperation, and providing real-world learning experiences. However, the implementation of role-play also faces several challenges, such as psychological barriers (anxiety and low self-confidence), insufficient teacher preparation and guidance, mismatch with student characteristics, and low levels of interaction in English. The effectiveness of this method is significantly influenced by the quality of the activity design, technological readiness, and the teacher’s ability to manage the learning process.